Biological characteristics of adipose‐derived stem cells from patients with progressive hemifacial atrophy: An in vivo study. (26th June 2022) - Gao, Qiuni; Qi, Zuoliang; Jin, Xiaolei; Yang, Zhenyu; Yu, Panxi; Yuan, Xihang; Hu, Yuling; Yang, Xiaonan
Abstract: Objective: In this study, we investigate the biological characteristics of ADSCs from patients with progressive hemifacial atrophy (PHA) in vivo and try to explore the theoretical support for cell‐assisted lipotransfer in treating patients with PHA. Methods: ADSCs and exosomes were respectively extracted from patients with PHA and healthy ones. PHA‐ADSC was detected the differentiation ability, phenotype, and anoxic resistance. NTA particle size, electron microscopy (TEM), and WB for CD63 and TSG10 were used to detect the exosomes. ADSCs of PHA (PHA‐ADSCs) and healthy ones (NORM‐ADSCs) mixed with their granular fat, exosomes mixed with PHA‐granular fat, and PBS mixed with PHA‐granular fat as the control group. The four groups of different grafts were, respectively, transplanted into nude mice, and the fat grafts were dissected and weighed at 2, 4, 8 and 12 w. Weight and volume retention were calculated for each of the four groups. Then, the four groups of fat grafts were tested for hematoxylin–eosin (HE) and immunohistochemical stainings, CD31 for blood vessel formation, CD68 for macrophage infiltration, and perilipin for fat formation, RT‐PCR analysis of the APRC5, ATG5, ATG7, ATG12, BAX, PPARG, CDKN1A, and CDKN2A genes. Results: ADSCs in the PHA group had typical phenotypes and multidirectional abilities. The PHA‐ADSCs ‐assisted lipotransfer group, exhibited a weaker droplet formation and lower volume retention rate than the NORM‐ADSCs‐assisted lipotransfer group but much better than the non‐cell‐assisted lipotransfer group. Exosome‐assisted lipotransfer group showed benefits, too. Conclusions: The PHA‐ADSCs‐assisted lipotransfer and the exosome‐assisted lipotransfer improved the fat survival rate after fat filling in patients with hemifacial atrophy. Cell‐assisted and exosome‐assisted lipotransfer is an effective method to treat hemifacial atrophy.